ANTIOPHIDIAN PROPERTIES EVALUATION OF ETHANOL EXTRACTAND FRACTIONS OBTAINED FROM Renealmia alpinia (Rottb) Mass (Zingiberaceae)CULTIVATED in vitro. - FERNÁNDEZ C., Maritza; ORTIZ C., William F.; PEREÁÑEZ J., Jaime A.; MARTÍNEZ R, Diego (Vitae, 2010)
Plant extracts are a rich source of pharmacologically active molecules. Their application allows a tradicional medicine approach to potential biological acitivities. This paper evaluates the inhibitory capacity of ethanolic extracts of leaves and little roots and also fractions chromatographically fractions obtained from Renealmia alpinia (Rottb) Mass, cultured in vitro, on the indirect hemolytic activity, proteolytic activity and coagulant activity induced by the Bothrops asper venom. Indirect hemolytic activity is inhibited to a greater extent by the fraction 7-8 (47.3 ± 2.20%) followed in order by the extracts from little roots (32.6 ± 6.90%) and leaves (24.2 ± 4.43%). They came from in vitro and ex vitro leaves (16.2 ± 3.88%). The proteolytic activity is largely inhibited by the leaves extracts in vitro and ex vitro without significant differences between them. Little roots in vitro showed the highest neutralization effect on coagulant activity (81.73 ± 9.949s). Proteolytic activity from Renealmia alpinia extracts on Bothrops asper venom is ruled out since there are not changes in the electrophoretic pattern of the venom. The results make possible the implementation of Renealmia alpinia as adjuvant for the treatment of ophidic accidents and sustain the value of micropropagation for mass production of active components.